PENGARUH DISIPLIN KERJA DAN JOB DESCRIPTION TERHADAP KINERJA KARYAWAN PADA PT.GIOVANI ABADI SENTOSA - Tarigan, Calista Feby; Sari, Sufika; Sitompul, Florencia Magdalena; Perangin-angin, Resa Wanda Sari Br (JURNAL GLOBAL MANAJEMEN, 2019)
The development of the era and the tight competition among companies require every company to run their companies optimally. That is why every company must well and thoroughly select their well qualified human resource for the success of the companies to reach their goals. Human resource is the main asset for organizations and the active agent of various activities in organizations and companies. Therefore the researcher used the variables of work discipline and job description on the employees’ performance of PT. Giovani Abadi Sentosa. This research was survey research with quantitative approach. The analysis method applied was Double Linear Regression Analysis. Samples used were eighty eight (88) employees and the sampling was done by using stratified sampling.The result of the study showed that work discipline and job description both had significant effect of employees’ performance. Estimate hypothesis coefficient used Adjusted R –2 as much as 44.9%. The variable of employee’s performance (Y) could be shown by the variation of Work Discipline variable (X1) and Job Description (X2) and the rest which was as much as 55,1% was other variables which were not tested in this research.